Mobile Weather Stations with Drone - Mohammad Zaid, Mohamad Nadzirul Ariff; Zohari, Mohd Hakimi (Progress in Engineering Application and Technology, 2024)
In contemporary weather monitoring, the fusion of innovative technologies like mobile weather stations and drones offers unprecedented capabilities for real-time data collection and analysis. This project aims to create a user-friendly dashboard for intuitive weather monitoring by combining the agility of drones with ground-based weather stations. The objectives include displaying crucial real-time information such as temperature, humidity, and barometric pressure, while ensuring an accessible interface for efficient data interpretation and analysis. The system utilizes an ESP32 microcontroller, various sensors, and the Blynk IoT platform for seamless connectivity. Through a systematic hardware setup and software integration, the prototype demonstrates the feasibility of a mobile weather station with drone collaboration, showcasing its potential in diverse applications, from agriculture to environmental research. The project's success highlights the promising future of integrated technologies for advanced weather monitoring and analysis